Resilient health reforms in times of permacrisis: the Greek citizens’ perspective - Souliotis, Kyriakos; Papadonikolaki, Jenny (Frontiers in Political Science, 2024)
This study investigates Greek citizens’ attitudes toward the current healthcare system and their perspectives on healthcare reforms. Additionally, it explores the role of both endogenous and exogenous crises in accelerating the implementation of long-overdue structural reforms that might otherwise be challenging to achieve. To this end, the research examines the level of trust in institutions and the implementation of healthcare reforms following the fiscal crisis and during the COVID-19 pandemic. The findings reveal that while most Greek citizens recognize the necessity of structural reforms within the healthcare system, approximately half of the population views these changes negatively. The primary obstacles to successful reform are identified as a lack of political will and resistance from specific interest groups. The contradiction within Greek society concerning healthcare reform is largely driven by low levels of institutional trust and social capital. Although there is a clear need for radical reforms, public perception tends to be negative when these changes are framed within political discourse. However, when reforms align with the actual needs of society, citizens’ trust in institutions increases, thereby improving the likelihood of successful policy implementation. This underscores the critical role of institutional trust in facilitating significant healthcare policy transformations.